Implikasi Pemikiran Ahmad Imam Mawardi Tentang Fiqh Minoritas Terhadap Pendidikan Moderasi Beragama di Kalangan Muslim Bali - Mochammad Muzakki Alwi; Muh. Sabilar Roysad (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study explores the concept of fiqh minoritas as formulated by Ahmad Imam Mawardi and its relevance to the development of Islamic education for Muslim minority communities in Bali. Using a qualitative-descriptive approach through library research, this study examines Mawardi’s perspective that places maqāṣid al-syarī‘ah (the objectives of Islamic law) and legal flexibility at the center of jurisprudential reasoning for Muslim minorities. The research finds that fiqh minoritas offers contextual legal principles that allow for adaptive practices in areas of worship, socio-political participation, cultural interaction, and economic engagement without compromising Islamic values. In the context of Bali, where Muslims live as a religious minority, this concept aligns well with existing educational strategies that emphasize tolerance, local cultural integration, and nonformal Islamic learning. The findings demonstrate that fiqh minoritas not only fosters religious moderation but also strengthens the resilience and positive contribution of Muslim minorities in a pluralistic society. This study concludes that Ahmad Imam Mawardi’s framework is theoretically robust and practically applicable for shaping inclusive, adaptive, and harmonious Islamic education in minority regions such as Bali.